Text and Image Proceedings of the 61e Rencontre Assyriologique Internationale, Geneva and Bern, 22-26 June 2015 - Attinger, Pascal; Cavigneaux, Antoine; Mittermayer, Catherine; Novák, Mirko (Orbis Biblicus et Orientalis. Series Archaeologica, 2018)
This book contains the proceedings of the 61e Rencontre Assyriologique Internationale, which was held in Geneva and Bern in Switzerland from 22nd until 26th June 2015. The overarching conference theme "Text and Image" addressed a topic of fundamental importance for historical research on ancient Near Eastern cultures and societies. The aim of the conference was to stimulate an interdisciplinary dialogue between the closely related, but increasingly diverging disciplines of Near Eastern Archaeology and Assyriology. Fifty-one articles are published in three languages, including contributions to the main topic and to a number of workshops organized in the context of the RAI, as well as reports on an extraordinary session devoted to cultural heritage.